2018
DOI: 10.1259/bjr.20180097
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of practical radiobiological modelling

Abstract: A summary of the key aspects of radiobiological modelling is provided, based on the theoretical and practical concepts of the linear quadratic (LQ) model, which gradually replaced other numerical approaches. The closely related biological effective dose (BED) concept is useful in many clinical applications. BED formulations in conventional photon-based radiotherapy continue to be developed, and can be extended to the now increasingly used proton and ion-beam therapy, to very low or high dose ranges, the dose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The utility of the LQ model in providing safe limits for avoiding radionecrosis in spinal cord tissue over a large range of dose fractionation schedules, with suggested methods for incorporating a transition to linearity with increasing dose in BED equations are presented by Jones and Dale in the same volume of this special edition. 23 There needs to be greater discussion of this topic and consensus decisions taken by informed specialists and patient representatives. The model can be presented for clinical use in different ways, by suggesting modified dose or percentages by which dose should be reduced or increased relative to a standard time (which could be, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the LQ model in providing safe limits for avoiding radionecrosis in spinal cord tissue over a large range of dose fractionation schedules, with suggested methods for incorporating a transition to linearity with increasing dose in BED equations are presented by Jones and Dale in the same volume of this special edition. 23 There needs to be greater discussion of this topic and consensus decisions taken by informed specialists and patient representatives. The model can be presented for clinical use in different ways, by suggesting modified dose or percentages by which dose should be reduced or increased relative to a standard time (which could be, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Linear Quadratic (LQ) model for cell kill is commonly used in radiotherapy for quantitative predictions dose/fractionation dependencies (Jones and Dale, 2018). There are two important parameters to cell kill in the LQ formalism, embodied in the equation:…”
Section: Linear Quadratic Model For Fractionated Radiotherapymentioning
confidence: 99%
“…Radioresistant cells have low α/β ratios. Larger doses per treatment are often suggested for low α/β systems and small doses per fraction for high α/β systems (Jones and Dale, 2018). A summary of the 5 'Rs' dose rate and LET effects on fractionated radiotherapy is provided in Table 1.…”
Section: Radiosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, mathematical modelling, which included RBE within biological effective dose (BED) equations, showed that neutrons would only be capable of improving clinical outcomes in the case of the treatment geometry provided by very superficial cancers with little normal tissue coverage (31), exactly the condition for air sinus and parotid tumours. The further extension of BED equations that contain RBE allowances in many radiobiological settings has the potential for guiding clinical practice (32), and the relevant equations are given below and in the Appendix. These BED equations used the RBEmax and RBEmin concepts in conjunction with the reference radiation tissue α/β ratio, which are known with greater confidence than the much higher neutron α/β values.…”
Section: Mathematical Modellingmentioning
confidence: 99%